Solar Energy Potential in Pannonian Part of Serbia and Croatia - Branka Nakomčić-Smaragdakis; Šljivac, Damir; Katić, Vladimir; Tijana Stajić; Zoran Čepić; Danijel Topić; Marko Vukobratović (International Journal of Electrical and Computer Engineering Systems, 2012)
Renewable energy sources have their share in the energy balance of almost every country, but not as much as they should compared to the given energy potential, although they allow the application of clean technologies and pollution reduction, reduce energy dependence on fossil fuel markets and enable the development of new technologies and supporting infrastructure that create new jobs. The primary interest of society as a whole is a rational energy use. With increasing population and growing demands for energy production and consumption, as well as the fact of the limited fossil fuel resources whose utilization leads to environmental pollution (the emergence of the greenhouse effect and global warming) there is an interest in increasing the participation of renewable energy sources (RES ) in energy sector. A share of RES in the energy balance of the country has its own energy, socio-economic and environmental benefits. RES provides application development and deployment of new technologies and supporting infrastructure, and therefore enables possibilities for new jobs, which directly contributes to economic development at local, regional and national level.